(untitled) (International Journal of Multidisciplinary Perspectives in Higher Education, 2021)
Studies on teacher leadership have stressed the need for democratic and motivating environment in school, professional development opportunities, reflection and peer observation, and learning environment as preconditions for leadership development. However, teachers are deprived of such professional development scenarios in the context of Nepal. Despite this, some of the teachers have performed exceptionally well in Nepal. Hence, this qualitative study analyzed the lived experience of three English language teachers from Nepal employing activity theory envisioned by Engestrom as a research lens to explore their professional development journey. The study discovered that to become a successful teacher leader, communication and instructional competence is must because it provides visibility of prospective teacher leaders among colleagues and the wider community initially. Further, reflection and sharing among colleagues, we found, were instrumental in the development process of teacher leaders. This article reveals that leadership is the manifestation of co-construction of an individual in a complex ecosystem of learning communities and hence the notion of leadership is emergent and fluid.